Efeito de supressão das emissões otoacústicas evocadas por estímulo transiente em lactentes de risco nascidos pré-termo - Amorim, Aline Mizozoe de (2007)
Objective: The objective of this research was to study the occurrence and magnitude of the transient otoacoustic emissions suppression in pre-term infants of high risk for hearing loss. Methods: The was carried out in 15 preterm infants. The equipment used was the ILO USB II V6 Clinical OAE Software from Ododynamics. The stimulation used was linear click presented at the intensity of 60 dB pe SPL (± 5). The contralateral noise (white noise) was at 60 dB SPL (± 5). Results: The results showed that there was significant statistical difference between the sides of the ears, with bigger magnitude of the suppression on the right ear and sex, with bigger magnitude of suppression on the masculine sex. Conclusions: The white noise presented contralaterally reduced the response level of the transient otoacoustic emissions, demonstrating the participation of efferent system for de effect was 93,3% on the studied population, being 66.6% for both ears and 33.4% for only of the ears. The average magnitude of the suppression was 2,1 dB SPL for the right ear and 1,3 dB SPL for the left ear. It did not have difference in the magnitude of suppression between the groups, according to gestacional age (p=0,8411). For group 1 and group 2 according to chronological age, had significant statistical difference (p= 0,457) being the magnitude of bigger suppression in group 2